Project-Based Learning With Digital Storytelling To Improve Science Literacy Of 10th-Grade Students In Ma Al Manshuriyah School - Munawar, Rizal Muharam; Jaenudin, Dadang; Retnowati, Rita (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
Abstract: This study aims to describe the effectiveness of the project-based learning (PJBL) model with digital storytelling to enhance science literacy among 10th-grade students on ecosystem subjects. The research design was a quasi-experimental non-equivalent pretest-posttest control group. The study was conducted at MA Al Manshuriyah with 57 participants from two classes, IPA 1 and IPA 2. IPA 1 was selected as the experimental group that used a project-based learning model with digital storytelling, while IPA2 was the control group that used a conventional learning model. Validation and judgment of the research instruments were performed by experts until they were deemed suitable for use. The results showed that the learning process made the students more active in creatively solving problems. There was an improvement in students' science literacy skills on ecosystem subjects with an N-gain score of 65% (experimental group) and 56% (control group). The percentage of good category in science literacy for the experimental group was 85%, while for the control group was 78%. Students' caring attitude towards the environment was obtained at 79% with a very good category. The researchers concluded that project-based learning with digital storytelling was effective in enhancing students' science literacy skills and raising awareness of the environment